INSTABILITAS TATA KELOLA KELAUTAN DAN PERIKANAN: PERIZINAN, KEWENANGAN DAN DAMPAK TERHADAP MASYARAKAT PESISIR - Baskoro, Aji; Hofifah, Hofifah (Badan Pembinaan Hukum Nasional, 2023)
Marine and fisheries governance in Indonesia has experienced significant changes in regulations, starting from Law No. 31 Year 2004, Law No. 45 Year 2009, to the Job Creation Law. These regulatory dynamics affect aspects such as licensing, authority, and the impact on fishermen and coastal communities. This research uses a normative juridical approach to analyse and reveal instability in marine and fisheries governance, with a conceptual approach to develop theoretical concepts that explain the complexity of these issues. The results show a regulatory shift to a risk-based licensing approach and centralisation of authority to the central government. Centralisation of licensing can create challenges for local coastal communities, which are geographically closer to the local government. Difficulties in accessing information, participation, and lack of rapid response are the main obstacles. Policy reviews and adjustments need to be made regularly to address instability and inequality. Shifts in licensing and authority must take into account environmental and social aspects in addition to economics. Involvement of stakeholders and coastal communities in the policy change process is key, with transparency and effective communication as key elements of success.